2006
DOI: 10.1093/annonc/mdl048
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability and methylation of the DNA mismatch repair genes in head and neck cancer

Abstract: Our results indicate that microsatellite instability and modifications in the hMLH1 and hMSH2 genes are implicated in a significant proportion of the patients with head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 29 publications
6
35
0
Order By: Relevance
“…In other cancer types MSI has been identified but remains poorly defined, for instance in squamous cell carcinomas. Hypermethylation of MLH1 and MSH2 genes have been implicated as a potential cause of MSI in head and neck squamous cell carcinoma [11]. In ovarian cancer, alterations of homologous repair genes including BRCA1 have been associated with CD274 expression and tumor-infiltrating lymphocytes [12].…”
Section: Introductionmentioning
confidence: 99%
“…In other cancer types MSI has been identified but remains poorly defined, for instance in squamous cell carcinomas. Hypermethylation of MLH1 and MSH2 genes have been implicated as a potential cause of MSI in head and neck squamous cell carcinoma [11]. In ovarian cancer, alterations of homologous repair genes including BRCA1 have been associated with CD274 expression and tumor-infiltrating lymphocytes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Methylation of different genes acting in independent pathways have been analyzed in HNC (Sanchez-Caspedes et al, 2000;Rosas et al, 2001;Hasegawa et al, 2002;Ogi et al, 2002;Fan, 2004;Demokan et al, 2006). However, most of these studies have focused on a single or, at most, a few candidate genes; and the reported methylation frequencies and specificities of the methods vary widely between the studies.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80-90% of cases of HNSCC are attributed to prolonged tobacco and/or alcohol use (2). However, only a small fraction of those who consume tobacco or alcohol develop this disease, suggesting that genetic factors are also important in its pathogenesis (4)(5)(6). Fundamental to the genetic basis of all cancers is the overexpression of oncogenes and/or silencing of tumor suppressor genes.…”
Section: Introductionmentioning
confidence: 99%